Leukocyte inflammatory phenotype and function in migraine patients compared with matched non-migraine volunteers: a pilot study - Hongtao Li; Qiang Fu; Kamaira Philips; Yufei Sun; Keturah R. Faurot; Susan A. Gaylord; John Douglas Mann (BMC Neurology, 2022)
Abstract Background Migraine is a neurological condition characterized by chronic inflammation. However, not much is known about the potential role of peripheral blood immune cells in the pathophysiology of migraine. Methods We investigated the status of peripheral blood immune cells of 15 adults with frequent episodic or chronic migraine recruited chronologically from a randomized clinical trial (RCT) on Nutrition for Migraine (NCCIH 5R01AT007813-05) and 15 non-migraine, healthy volunteers (control) matched by age, gender, and Body Mass Index (BMI). Continuous variables were presented as means ± standard deviationas well as medians, and comparisons between patients and healthy volunteers were performed with non-parametric Wilcoxon signed rank tests. Statistical analysis was performed using Stata (StataCorp. 2019. Stata Statistical Software). Fluorescence-Activated Cell Sorting (FACS) data were processed using FlowJo software (Ashland, OR: Becton, Dickenson and Company; 2019). Results We observed that migraineurs had a significantly lower percentage of non-classical monocytes (CD14+CD16++) in blood circulation, compared to the control group. In addition, Migraineurs also showed a significantly lower percentage of blood CD3+CD4+ helper T cells and CD4+CD25+ regulatory T cells, compared to controls. Differences in leukocyte surface markers between chronic migraine patients and their matched controls were more prominent than those between episodic migraine patients and their matched controls. Conclusions Our results suggest that migraine is associated with dysregulated peripheral immune homeostasis and that inflammation and autoimmunity may play a role in its pathophysiology.